Efektivitas Implementasi Badan Penyelenggaraan Jaminan Sosial (BPJS) Serta Dampaknya Terhadap Kesehatan Dan Ekonomi Masyarakat Tahun 2009-2013 Dan 2015-2019. - Desy Indriani (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2020)
This study aims to determine the level of effectiveness of the implementation of the Social Security Administration (BPJS), the success of the BPJS, the benefits of the BPJS and the impact of the existence of BPJS on the health and economy of the community with the object of research in 33 provinces in Indonesia in the 2009-2013 and 2014-2019 periods. This study uses secondary data taken from the publication of the Central Statistics Agency (BPS). In order to achieve the research objectives, this study used the method of effectiveness testing and pair difference test (Paried Sample t-test). The results of this study indicate that the level of BPJS participation, use of health fund allocations, subsidies provided to BPJS and health facilities have been effective in their implementation. Where the results of the pairwise difference test show that 5 provinces have an impact before and after the BPJS national health program and 28 provinces there is no impact from before and after the BPJS national health program on public health. As for the people's economy, 28 provinces had impacts before and after the BPJS national health program and 5 provinces had no impacts before and after the BPJS national health program.